The camera as a way of telling stories with images in 360 animations using VR technology - Białek, Maciej; Wiśniewska, Aneta; Szrajber, Rafał (Wydawnictwo Politechniki Łódzkiej, 2021)
VR technologies have found their place into the film industry, potentially revolutionizing standards of cinematography. Aim of this work was to investigate and compare the perception of space depending on the type of the camera. For this purpose, a special 360° animated film was created with two types of camera: one following the viewpoint of a character and another one defined by shots. As a result we can tell that the following camera seems to be more attractive to a recipient, which means a greater portion of a material was perceived and with a greater comfort of viewing experience.
Keywords: virtual reality; virtual camera; 360 degrees animation; space perception; wirtualna rzeczywistość; wirtualna kamera; animacja 360 stopni; postrzeganie przestrzeni